Benchmark testing of numerical approaches for modelling the influence of undercut depth on caving, fracture initiation and subsidence angles associated with block cave mining. (September 2014) - Woo, K.-S.; Eberhardt, E.; Elmo, D.; Stead, D.; Kaiser, P. K.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reports the findings from a benchmark study testing several numerical methods, with a focus on the influence of undercut depth on block caving-induced surface deformation. A comparison is drawn between continuum v. discontinuum treatments of the modelled geology. Results were evaluated with respect to different simulated levels of ground disturbance, from complete collapse to small-strain subsidence. The results show that for a given extraction volume, the extent of ground collapse at surface decreases as undercut depth increases. The presence of sub-vertical faults was seen to limit the extent of the modelled caving zones. In contrast, the extent of small-strain surface subsidence was seen to increase with increasing undercut depth. The faults in this case did not have the same limiting effect. Overall, the findings emphasise the importance of balancing model simplification against the need to incorporate more complex and computationally demanding representations of the rock mass structure.